2020
DOI: 10.1177/0306624x20909207
|View full text |Cite
|
Sign up to set email alerts
|

Rural-to-Urban Migration, Strain, and Bullying Perpetration: The Mediating Role of Negative Emotions, Attitude Toward Bullying, and Attachment to School

Abstract: Based on an integrated general strain theory, this study involved testing negative emotions (i.e., anxiety and depression), a social learning variable (i.e., attitude toward bullying), and a social control variable (i.e., attachment to school) as possible mediators of the strain–bullying relationship. A group comparison was also conducted to examine possible differences between migrant and non-migrant children. Data used in the study were derived from a questionnaire survey with a school-based multistage rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 73 publications
1
11
1
Order By: Relevance
“…We inferred that higher levels of strain directly lead to a desire for cyberbullying behavior, and cyberbullying victims were at increased risk of involving in delinquency. These align with GST and previous studies, and our results extend the existing theory on this relationship by examining both youth and adults samples, as previous studies have largely discussed this issue among adolescent samples, including a study did in China with minors ( Cui and To, 2021 ). In particular, we observed that the strain had a greater influence on cyberbullying victims.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We inferred that higher levels of strain directly lead to a desire for cyberbullying behavior, and cyberbullying victims were at increased risk of involving in delinquency. These align with GST and previous studies, and our results extend the existing theory on this relationship by examining both youth and adults samples, as previous studies have largely discussed this issue among adolescent samples, including a study did in China with minors ( Cui and To, 2021 ). In particular, we observed that the strain had a greater influence on cyberbullying victims.…”
Section: Discussionsupporting
confidence: 91%
“…For cyberbullying research, studies have provided a standard view, stating that engagement in cyberbullying was the result of physical, emotional, or psychological strain ( Jang et al, 2014 ; Lianos and McGrath, 2018 ), and participation in cyberbullying through strain-based factors (e.g., receiving bad grades, being treated unfairly by someone, victimization, and relationship issues) was a response to strain ( Patchin and Hinduja, 2011 ). Specifically, Cui and To (2021) used a school-based multistage random sample of 1,666 children in Grades 4 to 9 in China (Nanjing and Guangzhou), indicating that the experience of cyberbullying victimization, which can be a deviant motivation, has frequently been recognized as a reason of strain which can predict cyberbullying perpetration. Consequently, this study mainly focuses on how do the negative emotion and the low self-control affect cyberbullying between different roles in the Chinese context.…”
Section: Introductionmentioning
confidence: 99%
“…Though we did not find an association between the severity of peer victimization and subsequent bullying perpetration, we did find that depression and behavioral challenges were related to bullying perpetration severity. A recent study grounded in the general strain theory found that youth experiencing higher strain related to struggling academically and socially were more likely to engage in bullying perpetration (Cui & To, 2020). Notably, this relationship was mediated by attitudes towards bullying.…”
Section: Gender Interactions In the Prediction Of Bullying Perpetrationmentioning
confidence: 98%
“…Chen, 2017; Gao et al, 2016; Wang et al, 2020) and migrant children in specific (e.g. Cui and To, 2021; Lo et al, 2018). Nevertheless, except for one study (Zhen et al, 2020), previous research has not specifically tested the applicability of GST on LBC who presumptively suffer higher levels of strain and emotional hardship due to separation from parents.…”
Section: Introductionmentioning
confidence: 99%